CtcRbase: the gene expression database of circulating tumor cells and microemboli. (15th April 2020) - Zhao, Lei; Wu, Xiaohong; Li, Tong; Luo, Jian; Dong, Dong
Abstract: Circulating tumor cells/microemboli (CTCs/CTMs) are malignant cells that depart from cancerous lesions and shed into the bloodstream. Analysis of CTCs can allow the investigation of tumor cell biomarker expression from a non-invasive liquid biopsy. To date, high-throughput technologies have become a powerful tool to provide a genome-wide view of transcriptomic changes associated with CTCs/CTMs. These data provided us much information to understand the tumor heterogeneity, and the underlying molecular mechanism of tumor metastases. Unfortunately, these data have been deposited into various repositories, and a uniform resource for the cancer metastasis is still unavailable. To this end, we integrated previously published transcriptome datasets of CTCs/CTMs and constructed a web-accessible database. The first release of ctcRbase contains 526 CTCs/CTM samples across seven cancer types. The expression of 14 631 mRNAs and 3642 long non-coding RNAs of CTCs/CTMs were included. Experimental validations from the published literature are also included. Since CTCs/CTMs are considered to be precursors of metastases, ctcRbase also collected the expression data of primary tumors and metastases, which allows user to discover a unique 'circulating tumor cell gene signature' that is distinct from primary tumor and metastases. An easy-to-use database was constructed to query and browse CTCs/CTMs genes. ctcRbase can be freely accessible at http://www.origin-gene.cn/database/ctcRbase/ .